Serious Games and Edutainment Applications - Ma, Minhua; Andreas Oikonomo; Lakhmi C. Jain (Springer eBooks., 2011)
The recent emergence of serious games as a branch of video games and as a promising frontier of education has introduced the concept of games designed for a serious purpose other than pure entertainment. To date the major applications of serious games include education and training, engineering, medicine and healthcare, military applications, city planning, production, crisis response, to name just a few. If utilised alongside, or combined with conventional training and educational approaches, serious games could provide a more powerful means of knowledge transfer in almost every application domain. Serious Games and Edutainment Applications offers an insightful introduction to the development and applications of games technologies in educational settings. It includes cutting-edge academic research and industry updates that will inform readers of current and future advances in the area. The book is suitable for both researchers and educators who are interested in using games for educational purposes, as well as game professionals requiring a thorough understanding of issues involved in the application of video games technology into educational settings. It is also applicable to programmers, game artists, and management contemplating or involved in the development of serious games for educational or training purposes.